Leading Teams : Tools and Techniques for Successful Team Leadership from the Sports World - Guenzi, Paolo (Wiley, 2013)
Important new insights on team leadership and motivation, along with powerful tools and techniques taken from the world of sports How do the sports world's most successful coaches instill their teams with esprit de corps, a collaborative mindset, and an unbeatable desire to win? More importantly, what can business leaders and managers learn from their example? This book answers these and a host of key questions about what it takes to be a successful leader in business or in sports. Drawing upon their unique experiences working with top sports coaches, as well as some of the world's le.